2004
DOI: 10.1016/j.socscimed.2003.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Women's menarche stories from a multicultural sample

Abstract: This paper reports on the findings of a focus group study that examines how women have experienced menarche at the personal level and in relation to the larger cultural, religious, and societal environment. Fifty-three women from 34 different countries were recruited in 13 focus groups. On the one hand, at the personal level, menarche stories shared in this study revealed salient themes concerning feelings experienced at the time of menarche, the importance of mother's reactions to their daughter's first menst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
100
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 29 publications
10
100
0
2
Order By: Relevance
“…As found here and supported by other studies (Amaral, 2011;Beausang & Razor, 2000;Koff & Rierdan, 1995;Rembeck & Hermansson, 2008;Uskul, 2004), for women, one's mother is seen as the primary source of information, as well as emotional and practical support, when reaching menarche. Furthermore, we found that one's mother plays an essential role in how women relate to the menstrual phenomenon later in life.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As found here and supported by other studies (Amaral, 2011;Beausang & Razor, 2000;Koff & Rierdan, 1995;Rembeck & Hermansson, 2008;Uskul, 2004), for women, one's mother is seen as the primary source of information, as well as emotional and practical support, when reaching menarche. Furthermore, we found that one's mother plays an essential role in how women relate to the menstrual phenomenon later in life.…”
Section: Discussionsupporting
confidence: 89%
“…Menarche is associated with sexual maturation, symbolizes the transition from childhood to womanhood and is a unique experience for every woman. However, many young girls express sadness at not being ready to become a woman when reaching menarche (Lee, 2009;Orringer & Gahagan, 2010;Rembeck & Hermansson, 2008;Uskul, 2004). Menopause is a part of the midlife changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Feelings and attitudes about menarche that is the sign of transition to adolescence include sociocultural differences (Chrisler and Zittel, 1998, Uskul 2004, Lee, 2008, Chang et al, 2010. First emotional responses to menarche are; fear 35.2%, astonishment 35.8%, embrassment 6.8%, sorrow 4.5%, and rejoice 10.1% in our study.…”
Section: Discussionmentioning
confidence: 54%
“…First emotional responses to menarche are; fear 35.2%, astonishment 35.8%, embrassment 6.8%, sorrow 4.5%, and rejoice 10.1% in our study. Fear, sorrow, embrassment, feelings herself dirty, and such negative feelings are stated as the first responses to menarche at many national and international studies (Tang et al, 2003, Demirel and Terzioglu, 2003, Uskul, 2004, Jorm et al, 2004, Tortumluoglu et al, 2004, Yeung et al, 2005, Deo and Ghattargi, 2005, Turan and Ceylan, 2007, Chang et al, 2010, Ozdemir et al, 2011, Mcmahan et al, 2011.…”
Section: Discussionmentioning
confidence: 99%